Penilaian Kinerja Jaringan Irigasi Air Tanah Sumur PNK-219 Berdasarkan Indeks Penilaian Operasi dan Pemeliharaan pada Daerah Irigasi Desa Nunkurus - Cintana Rizka Totu; Amandus Jong Tallo; Yunus Fallo (Universitas Harapan Medan, 2026)
Groundwater Irrigation Networks (JIAT) play a significant role in ensuring water availability in areas with seasonal rainfall. This study evaluates the performance of the PNK-219 groundwater irrigation system in Nunkurus Village, Kupang Timur District, Kupang Regency, based on the operation and maintenance index stipulated in Ministerial Regulation of Public Works and Housing No. 12/2015 and Ministerial Regulation of Public Works and Housing No. 23/2015. A scoring method with weighted assessment was applied to six components: physical infrastructure, cropping productivity, supporting facilities, organizational personnel, documentation, and the Water Users Farmers Association (P3AT). Data were collected through field observation, inventory, interviews, and document analysis. The results indicate a performance index of 77.56%, classified as good. Physical infrastructure and documentation were rated good, while cropping productivity and organizational aspects were fairly good. Supporting facilities and institutional capacity of P3AT require improvement to ensure sustainable management. Overall, the system remains capable of meeting irrigation water demands and supporting agricultural productivity.